P105 THE PROGRESSION OF INFLAMMATORY BOWEL DISEASE THROUGHOUT LATIN AMERICA: A SYSTEMATIC REVIEW. (7th February 2019) - Kotze, Paulo G; Underwood, Fox; Damiao, Aderson O; Ferraz, Jose; Saad-Hossne, Rogerio; Toro, Martin; Iade Vergara, Beatriz M; Bosques-Padilla, Francisco; Teixeira, Fabio; Julian-Banos, Fabian; Simian, Daniela; Ghosh, Subrata; et al.
Abstract: Background: The incidence and prevalence of ulcerative colitis (UC) and Crohn's disease (CD) is stabilizing in the Western world, but increasing in developing countries. However, epidemiological data on IBD is lacking from Latin American countries. The aim of this systematic review is to summarize the clinical and epidemiological information on IBD arising from countries in Latin America. Methods: Three databases (MEDLINE, EMBASE, SciELO) were searched from the onset of the databases to September 12, 2018 for clinical or epidemiological data on IBD from all Latin American countries and territories. We assessed the following outcomes: incidence per 100, 000 person-years; prevalence per 100, 000 persons; ratio of patients diagnosed with UC versus CD (ratios greater than 1 favor UC); phenotype as defined by the Montreal Classification; proportion of population prescribed IBD medications (i.e., steroids, 5-ASA, immunomodulators, and anti-TNF agents); and proportion of the IBD population with an intestinal resection. Choropleth maps of the UC:CD ratio were created using Jenks Natural Breaks. Results: We identified 1, 434 abstracts with 126 articles selected for full-text review, and 61 articles were used for data extraction. Incidence and prevalence of IBD is steadily rising throughout Latin America. For example, the incidence of CD in Brazil rose from 0.08 in 1988 to 0.68 (1991-1995) to 5.5 per 100, 000 in 2015. The highest reported prevalence of IBD is in Argentina (2007) at 15 and 82 per 100, 000 for CD and UC, respectively. The UC:CD ratio exceeds 1 in all regions throughout Latin America with the exception of Brazil where the states of Alagoas, Rio de Janeiro, and Mato Grosso do Sul reported more CD than UC patients (Figure 1). The proportion of patients prescribed anti-TNF has steadily risen for CD (e.g. Brazil: 29.6% in 2005-2012 to 43.4% in 2014), but not UC (e.g. Brazil: 4.5% in 2014). Surgery for IBD is declining: e.g. in Chile, CD: 57.0% and UC: 18.0% in 1990–2002; and CD: 38.0% and UC: 5.0% in 2012 to 2015. In contrast, other regions showed stable colectomy rates pre- and post-introduction of anti-TNF for UC: e.g. in Peru, colectomy for UC 6.9% in 2001–2003 and 6.2% in 2004–2014 (Figure 2). Conclusions: The burden of IBD is expanding throughout Latin America. Heterogeneity between countries may offer important clues into the pathogenesis of IBD, as well as identify regions requiring standardization in management and healthcare delivery. Additional population-based epidemiologic studies are needed to better define the evolving burden of IBD throughout Latin America. Figure 1: UC:CD ratio in Latin America. Figure 2: Proportion of Crohn's disease (CD) and ulcerative colitis (UC) patients prescribed anti-TNF therapy and undergoing an intestinal resection in Latin America.